Hepatitis C Virus Infection and Mixed Cryoglobulinemia - Gianfranco Lauletta; Sabino Russi; Vincenza Conteduca; Loredana Sansonno (Clinical and Developmental Immunology)
Hepatitis C virus (HCV) chronic infection is recognized as the major cause of mixed cryoglobulinemia (MC). Its persistence represents a continuous stimulus for host immune system with production of circulating immune complexes (ICs), one-third of them with cryoprecipitate property. Several factors contribute to the biological activities of ICs, many of which are not completely known. Among them, complement factors play a crucial role in the cold-insoluble ICs-mediated vasculitis, involving primarily small blood vessels in different tissues including skin, kidney, peripheral, and central nervous system. Liver represents the major target of HCV infection with inflammatory infiltrates, resembling secondary lymphoid follicles. Cytokine like CXCL13 contribute to B-cell homing in intraportal lymphoid aggregates, in which B-cell clonal selection may arise. B-cell clonal expansion starts as an antigen-driven event and expands towards indolent and malignant B-cell proliferation. Occurrence of intrahepatic B-cell clonalities correlates with extrahepatic clinical manifestations of HCV infection. In this context, cryoglobulinemic patients should be considered a peculiar HCV-infected population that needs a clinical multidisciplinary approach and more articulated therapeutic measures.